Uveitis in patients with multiple sclerosis - Ahmed Mohamed Karara; Mai Sharawy; Tamer Ahmed Macky (Cairo : Ahmed Mohamed Karara, 2012)
This is a cross sectional observational descriptive clinical study , in which 75 patients diagnosed with MS ( of the Relapsing - Remitting type ) , according to McDonald criteria , underwent complete ophthalmological examination , in search for the presence and type of uveitis . Patients having any other ocular disease or any history of ocular surgery or trauma in either eye , were excluded from our study
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Ophthalmology
Issued also as CD
Keywords: Cytomegalovirus; Intravenous; Multiple sclerosis